Association Between Proficiency and Efficiency in Electronic Health Records Among Pediatricians at a Major Academic Health System - Saif Khairat; Saif Khairat; Lauren Zalla; Allie Gartland; Carl Seashore (Frontiers Media S.A., 2021)
Objective: The purpose of this study was to evaluate the variations in electronic health record (EHR) activity among General and Specialty pediatricians by investigating the time spent and documentation length, normalized for workload.Materials and Methods: We conducted a cross-sectional study of pediatric physicians using Epic EHR at a major Southeastern academic healthcare system. We collected user-level EHR activity data of 104 pediatric physicians over 91 days from April 1 to June 30, 2020.Results: Of the 104 pediatrics physicians, 56 (54%) were General pediatricians and 48 (46%) were Specialists pediatricians. General pediatricians spent an average of 17.6 min [interquartile range (IQR): 12.9-37] using the EHR per appointment, while Specialists spent 35.7 min (IQR: 28-48.4) per appointment.Significant negative associations were found between proficiency scores and the amount of time spent in the system for Generalists (p < 0.001). On the contrary, significant positive associations were found between proficiency scores and the amount of time spent in the system for Specialists (p < 0.01).Conclusions: We report an association between EHR proficiency and efficiency levels among pediatricians within the same healthcare system, receiving the same EHR training, and using the same EHR system. The profound differences in EHR activity suggest that higher priority should be given to redesigning EHR training methods to accommodate the learning needs of physicians.